La presencia de atrofia hipocampal en pacientes con neurocisticercosis calcificada y factores asociados - Sánchez Boluarte, Sofía Stefanie (2020)
Introduction: In endemic countries it is common to observe patients with calcified neurocysticercosis (NCC) associated with hippocampal atrophy, which in turn may be associated with treatment-resistant epilepsy, so this study sought to compare the frequency of hippocampal atrophy and explore factors associated with its presence, in patients with calcified NCC, viable NCC and in rural residents. Methods: One hundred ninety-seven individuals with calcified NCC, 38 with viable NCC and 197 rural residents older than 40 years were selected. The 432 resonances were read by two neuroradiologists and an expert neurologist in NCC; Then a regression analysis was performed using the generalized linear model, exploring the factors associated with hippocampal atrophy. Results: Hippocampal atrophy was more frequent in patients with calcified NCC than in patients with viable NCC (53/197, 26.9%, versus 3/38, 7.9%, PR 4.92, CI: 1.25-19.44, p=0.023) or in older rural residents. of 40 years (53/197, 26.9%, versus 16/197, 8.1%, PR 3.31, CI: 1.96-5.59, p>0.000). Conclusions: The frequency of hippocampal atrophy in patients with calcified NCC is 4 times more frequent than in patients with viable NCC or twice more frequent than in the general population, which suggests that hippocampal atrophy is associated with calcified NCC and could develop as a consequence of NCC.